Penafsiran Delik Makar dalam dinamika Rezim Pemerintahan di Indonesia - Ristanti, Yuni; Ahwan, Ahwan (Fakultas Hukum Universitas Hang Tuah, 2025)
The purpose of the research is to analyze the development of interpretation against treason/Makar offense on the Penal Code in the law enforcement in Indonesia. This study is a normative legal research which refers to the foundherentism theory and the interpretation of judges theory against enforcement, the supreme court‘s Verdict No. 574 K / Pid /2012, Verdict number 38 / pid.B /2011/PN.Wmn, verdict No. 07/Pid/2015/PT.AMB. The results of the research finds out that Makar offense has various meanings, Penal Code itself does not on strictly define what Makar offense is. It results in vague norms. Therefore, the interpretation against the article 106 of the penal Code relies on the development of the interpretation of the verdict about Makar offense. So far, various verdict interprets or connect Makar offense -as stipulated in article 106 of Penal Code- with subversion, independence, separatism (martial law i.e. terrorism and armed rebellion). Conducting an independence ceremony which is not an Indonesian independence ceremony, sticking a flag other than the Indonesian flag, an oration which increase the sense of nationality other than a sense of nationality towards the Indonesian state, producing a banner to commemorate the anniversary of independence instead of the Indonesian state.